AB0033 Association between radiographic joint damage and a PADI4 SNP in japanese RA patients. (23rd January 2014) - Yoshida, S.; Ikari, K.; Taniguchi, A.; Yamanaka, H.; Momohara, S.
Abstract : Background: Peptidyl arginine deiminase, type IV (PADI4) gene has been reported to be associated with susceptibility to rheumatoid arthritis (RA) mainly in Asian populations (1, 2). Objectives: To investigate the impact of peptidyl arginine deiminase, type IV (PADI4) gene on radiographic joint damage in Japanese rheumatoid arthritis (RA) patients. Methods: DNA samples of 865 RA patients were obtained from the IORRA (Institute of Rheumatology RA cohort) DNA collection. A SNP on PADI4, rs2240340, was selected for the study because it showed the best evidence of association to RA susceptibility in the tested population. Genotyping was performed with TaqMan genotyping assay (Applied Biosystems Japan). Radiographs of hands at 5-year disease duration were scored by the Sharp/van der Heijde score (SHS_hands). Since the distribution of SHS_hands is far from normal probability distribution, a logarithmic transformation is applied (ln_hands). ACPA status was assessed by ELISA and categorized as negative (<4.5 IU, upper limit of normal[ULN]), positive at low titers (<3 times ULN) and positive at high titers (>3 ULN). Linear regression analysis was performed with ln_hands as a dependent variable and the number of the risk alleles of rs2240340 as independent variables. Since ACPA status is known as a significant predictor of disease severity, linear regression analysis adjusted by ACPA status was also performed. These analyses were performed using the R software package. Results: The PADI4 SNP, rs2240340, was significantly associated with radiographic joint damage (P=0.01). The association between the number of risk alleles of the PADI4 SNP and ln_hands was also significant after adjusting with ACPA status (P=0.02). Conclusions: PADI4 gene is significantly associated with radiographic joint damage in Japanese RA patients. References: Functional haplotypes of PADI4, encoding citrullinating enzyme peptidylarginine deiminase 4, are associated with rheumatoid arthritis. Suzuki A, et al. Nat Genet. 34:395-402. Association between PADI4 and rheumatoid arthritis: a meta-analysis. Iwamoto T, et al. Rheumatology (Oxford). 45:804-7. Disclosure of Interest: S. Yoshida: None Declared, K. Ikari Grant/Research support from: Japanese Ministry of Education, Culture, Sports, Science, and Japanese Ministry of Technology, of Health, Labour and Welfare., Speakers Bureau: Mitsubishi Tanabe Pharma Corporation, A. Taniguchi: None Declared, H. Yamanaka Grant/Research support from: IORRA study is supported by 40 pharmaceutical companies; Asahikasei Kuraray Medical Co., Ltd., Abbott Japan Co., Ltd., Asahikasei Pharma Corporation, Astellas Pharma Inc., AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Daiichi Fine Chemical Co., Ltd., Daiichi Sankyo Co., Ltd., Dainippon Sumitomo Pharma Co., Ltd., Eisai Co., Ltd., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K., Japan Tobacco Inc., Kaken Pharmaceutical Co., Ltd., Kissei Pharmaceutical Co., Ltd., Kowa Pharmaceutical Co., Ltd., Maruho Co., Ltd., Mitsubishi Chemical Medience Corporation, Mitsubishi Tanabe Pharma Corporation, Mochida Pharmaceutical Co., Ltd., MSD K.K., Mundipharma K.K., Nippon Chemiphar Co., Ltd., Nippon Shinyaku Co., Ltd., Novartis Pharma K.K., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Sanwa Kagaku Kenkyusho Co., Ltd., Sekisui Medical Co., Ltd., Shionogi Co., Ltd., Taishotoyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Company Limited, Teijin Pharma Limited, Torii Pharmaceutical Co., Ltd., UCB Japan Co., Ltd., ZERIA Pharmaceutical Co., Ltd., Speakers Bureau: Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB, S. Momohara Speakers Bureau: Abbott Japan Co. Ltd., Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Santen Pharmaceutical Co. Ltd., and Mitsubishi Tanabe Pharma Corporation.